Can Assets Determine Family Happiness? - Purwaningsih, Vitriyani Tri (Journal of Economics Research and Social Sciences, 2021)
Ownership of assets can be assessed as the success of individual achievement in his life goals. It certainly can make individuals feel satisfied with the efforts they have made. Life satisfaction is one of the dimensions used by BPS to measure happiness. Thus, this study will analyze the effect of asset ownership on happiness. The data used in this study are data from the Indonesia Family Life Survey (IFLS) wave 5 of 2014. Analysis of the model in this study uses logistic regression for analysis in Java and outside Java Island. This study found that ownership of assets (jewelry, savings, vehicles, receivables), health, gender of the head of the household, type of residential, mobile phone, television, and access to the internet have a significant effect on household happiness. At the same time, other assets (houses/other buildings, land), number of household members, type of floor, and residential area (urban, rural) have no effect in determining of happiness of the household. The finding in this study also states that the probability of household happiness will be higher outside Java Island.